1995
DOI: 10.1002/j.1537-2197.1995.tb11584.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pollination success on floral longevity in the orchidCalypso bulbosa(Orchidaceae)

Abstract: The lifespan of an individual flower is often affected by pollination success. Species differ regarding whether male function (pollen removal), female function (pollen deposition), or both trigger floral senescence. We studied senescence in the singleflowered, deceptive orchid Calypso bulbosa by manipulating the degree of male and female reproductive success. We found that deposition of any amount of pollen resulted in dramatic changes in shape and color within 4 d, whereas unmanipulated flowers and those that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
3
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 30 publications
2
28
3
2
Order By: Relevance
“…This percentage of pollinia removal was considerably lower than those observed in E. palustris (60− 67%, Nilsson, 1978) and E. helleborine (up to 85%, Ehlers et al, 2002) in Sweden. Unlike the present work, previous studies in other orchids revealed that the rate of pollinia removal is higher than the fruit set (Schemske, 1980;Proctor and Harder, 1995). The low rate of pollinia removal observed in the present study would be attributable to only a 2-day survey and/or rarity of pollinators during the study period.…”
Section: Hand Pollination Experimentscontrasting
confidence: 93%
“…This percentage of pollinia removal was considerably lower than those observed in E. palustris (60− 67%, Nilsson, 1978) and E. helleborine (up to 85%, Ehlers et al, 2002) in Sweden. Unlike the present work, previous studies in other orchids revealed that the rate of pollinia removal is higher than the fruit set (Schemske, 1980;Proctor and Harder, 1995). The low rate of pollinia removal observed in the present study would be attributable to only a 2-day survey and/or rarity of pollinators during the study period.…”
Section: Hand Pollination Experimentscontrasting
confidence: 93%
“…This recorded period was obtained in cultivated experimental conditions (without environmental factor control) in which the pollination effect was not considered. Pollination usually reduces floral longevity by means of ethylene production (Stead 1992;Proctor & Harder 1995;van Doorn 1997;Arathi et al 2002), and it is a way to minimize the invested female resources and assure male fitness by reducing pollen-grain competition once the grains reach the stigmatic surface (Lankinen et al 2006). It is likely to assume that some variation in flower longevity found in T. polymorphum could be explained by this cause.…”
Section: Discussionmentioning
confidence: 99%
“…(Pijl & Dodson, 1966). In these plants, greater longevity is observed in non-pollinated flowers; pollination promotes rapid changes that induce floral senescence (Proctor & Harder, 1995;Martini et al, 2003;Abdala-Roberts et al, 2007). The long-lived orchid flowers have been interpreted as an adaptation to low pollinator activity (Stpiczynska, 2003), increasing the chances of pollination and thus the reproductive success (Pijl & Dodson, 1966;Martini et al, 2003).…”
Section: Introductionmentioning
confidence: 99%